Integrating In-Situ and Ex-Situ Data Management Processes for Biodiversity Conservation - Schwartz, Karin R.; Parsons, E. Christien M.; Rockwood, Larry; Wood, Thomas C. (Frontiers in Ecology and Evolution, 2017)
There is an increasing need for a “one plan approach” for conservation strategies that integrate in-situ and ex-situ management processes. Zoological institutions contribute directly to threatened species conservation through paradigms such as reintroduction, head-starting, supplementation, or rescue/rehabilitation/release. This in-situ/ex-situ integration necessitates collaboration at all levels of conservation action including planning, implementation, monitoring and finally assessment to drive adaptive management processes. Each component is dependent on the availability and accuracy of data for evidence to facilitate evaluation and adaptive management processes. The Zoological Information Management System (ZIMS), managed by Species360, is a centralized web-based information system used in zoological institutions worldwide to pool life history, behavior and health data and facilitate animal husbandry, health, and breeding management processes. Currently used for few integrated conservation programs, ZIMS is an innovative tool that offers a new opportunity to link data management processes for animals that spend a part of their lives under human care and part in their natural environment and great potential for use for managed wild populations.